Hand-assisted bilateral nephrectomy in a patient with adult polycystic kidney disease - Pinto, Marcello Alves (2002)
CONTEXT: Dominantly autosomal polycystic disease is characterized by multiple bilateral and nonfunctional cysts, which lead to progressive kidney failure. OBJECTIVE: Our objective was to report on a case of hand-assisted bilateral nephrectomy in a 28- year-old female patient with adult polycystic disease and recurring pyelonephritis in a kidney transplant program. CASE REPORT: A hand-assisted bilateral nephrectomy was performed through a supra-umbilical median incision of approximately 6 cm, and with 3 ports of 10 mm. The length of the surgery was 3 hours and 15 minutes. The kidneys were removed after the aspiration of some cysts through the supraumbilical incision. Pain control was achieved via the use of analgesics. The blood loss during surgery was 160 ml. During the postoperative period, the patient developed right-side pneumothorax, which was drained with no further occurrence. This drain was kept in place for 48 hours. The length of hospitalization was 4 days.